The Effectiveness of Infant Massage on Weight Gain of Preterm Infants - Pratiwi, Tika Ayu; Yusnanda, Febri; Susanti, Novi; Ilawati, Sri (International Journal of Public Health Excellence (IJPHE), 2024)
A preterm birth is a high-risk event occurring when the gestational age is less than 37 weeks. This can result in adverse outcomes, such as a low birth weight (LBW). The immaturity of the lungs in premature infants increases the likelihood of developing respiratory distress syndrome (RDS). To address this, it is essential to enhance nutritional fulfillment in premature babies with LBW and RDS through targeted intervention. This can be achieved through techniques like massage therapy and nesting installation, which have been shown to stimulate infants' growth and development. The objective of this case study is to determine the effectiveness of combined massage therapy and nesting in increasing the weight of premature babies with LBW accompanied by RDS. The research employed a case study approach. The subjects were premature babies with LBW accompanied by RDS in the perinatology room of the National Referral Hospital in Indonesia. This case study revealed that combined massage and nesting therapy resulted in a 6.1%–7.8% increase in body weight and a stabilization of oxygen saturation from days one to three of therapy. This outcome can be attributed to the fact that massage stimulates the release of gastrointestinal hormones that contribute to weight gain, and that nesting encourages the production of growth hormones resulting from restorative sleep. The integration of these two therapies has been found to significantly enhance body weight and maintain oxygen saturation levels within an optimal range. It is therefore evident that the role of nurses as nursing care providers must be enhanced in order to provide the necessary stimulation interventions for premature babies with LBW accompanied by RDS.